2017
DOI: 10.1534/genetics.116.186759
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair inDrosophila: Mutagens, Models, and Missing Genes

Abstract: The numerous processes that damage DNA are counterbalanced by a complex network of repair pathways that, collectively, can mend diverse types of damage. Insights into these pathways have come from studies in many different organisms, including Drosophila melanogaster. Indeed, the first ideas about chromosome and gene repair grew out of Drosophila research on the properties of mutations produced by ionizing radiation and mustard gas. Numerous methods have been developed to take advantage of Drosophila genetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
128
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 194 publications
(204 reference statements)
4
128
2
Order By: Relevance
“…Drosophila melanogaster presents an interesting case where the GGR pathway for NER is present but TCR was thought to be missing (11, 12). The lack of fly homologs for genes required for TCR in other organisms — CSA/ERCC8 and CSB/ERCC6 — suggested that the pathway was lost during evolution (11).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster presents an interesting case where the GGR pathway for NER is present but TCR was thought to be missing (11, 12). The lack of fly homologs for genes required for TCR in other organisms — CSA/ERCC8 and CSB/ERCC6 — suggested that the pathway was lost during evolution (11).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated level of DNA damages under dehydration has been reported for different species, including Diptera [69][70][71]. The damage-induced DNA repair may also intensify recombination due to the upregulation of some common enzymatic pathways [72,73].…”
Section: (C) Desiccation-induced Changes In Recombination Rate and Thmentioning
confidence: 98%
“…Thanks to CRISPR/Cas technology, generating such mutants has become within the reach of any research laboratory. Indels are readily created by inducing two site-specific double strand breaks (DSBs), thus deleting the intervening genomic sequences ( [4]). With this approach, any gene can be inactivated in most model organisms and the phenotypic consequences assessed.…”
Section: Introductionmentioning
confidence: 99%